2013
DOI: 10.1007/s00394-013-0625-4
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and treatment effects of a hemp seed (Cannabis sativa L.) meal protein hydrolysate against high blood pressure in spontaneously hypertensive rats

Abstract: The results suggest that HMH with strong hypotensive effects in SHRs could be used as a therapeutic agent for both the prevention and treatment of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 29 publications
2
68
0
Order By: Relevance
“…For example, enzymatic food protein hydrolysates and peptides with antihypertensive activities have been widely demonstrated García-Tejedor et al, 2014;He, Alashi, Malomo, et al, 2013;He, Malomo, Alashi, et al, 2013;He, Malomo, Girgih, Ju, & Aluko, 2013;Huang, Sun, He, Dong, & Li, 2011;Li et al, 2011;Majumder et al, 2013;Yamada et al, 2013). Some of the reports have also shown that the blood pressure-lowering effect of the food protein hydrolysates and peptides is related to direct in vivo reduction in plasma ACE and renin activities (García-Tejedor et al, 2014;Girgih, Alashi, He, Malomo, & Aluko, 2014;Huang et al, 2011). A recent report has shown the uptake of a casein-derived peptide (HLPLP) from the gastrointestinal tract into rat blood, which confirms that some of these food protein-derived peptides could be bioavailable .…”
Section: Introductionmentioning
confidence: 91%
“…For example, enzymatic food protein hydrolysates and peptides with antihypertensive activities have been widely demonstrated García-Tejedor et al, 2014;He, Alashi, Malomo, et al, 2013;He, Malomo, Alashi, et al, 2013;He, Malomo, Girgih, Ju, & Aluko, 2013;Huang, Sun, He, Dong, & Li, 2011;Li et al, 2011;Majumder et al, 2013;Yamada et al, 2013). Some of the reports have also shown that the blood pressure-lowering effect of the food protein hydrolysates and peptides is related to direct in vivo reduction in plasma ACE and renin activities (García-Tejedor et al, 2014;Girgih, Alashi, He, Malomo, & Aluko, 2014;Huang et al, 2011). A recent report has shown the uptake of a casein-derived peptide (HLPLP) from the gastrointestinal tract into rat blood, which confirms that some of these food protein-derived peptides could be bioavailable .…”
Section: Introductionmentioning
confidence: 91%
“…The specific health‐promoting activities include angiotensin I‐converting enzyme (ACE) inhibition, renin inhibition, acetylcholinesterase (AChE) inhibition, metal‐binding capacity, antioxidant activity, hypocholesterolemic effect, and serum glucose regulation. The bioactivity is elicited through the hydrolysis with gastrointestinal enzymes (pepsin, pancreatin, and trypsin) (Aiello et al., ; Girgih et al., ,b; Girgih, Alashi, He, Malomo, & Aluko, ; Girgih, He, & Aluko, ; Girgih, Udenigwe, & Akuko, , ; Girgih, Udenigwe, Li, Adebiyi, & Aluko, ; Zanoni, Aiello, Arnoldi, & Lammi, ) or exogenous proteases such as alcalase, papain, flavourzyme, neutrase, and thermolysin (Hadnađev et al., ; Lu et al., ; Malomo & Akuko, ; Malomo, Onuh, Girgih, & Aluko, ; Tang, Wang, & Yang, ; Wang, Tang, Chen, & Yang, ). Peptides with ACE inhibitory activity have also been produced from hemp protein with acid hydrolysis (Orio et al., ).…”
Section: Nutrition and Health Benefits Of Hempseed Proteinmentioning
confidence: 99%
“…Girgih et al, 2011b r Plasma ACE activity was remarkably suppressed in hempseed meal protein hydrolysate (HMH)-fed rats compared to control rats. Girgih et al, 2014a r HT (bacterial) produced the highest ACE-inhibitory activity of alkali-and acid-extracted HPI among all microbial and plant proteases (AFP, HT, protease G, actinidin, and zingibain). Teh et al, 2016 r Four peptides (GVLY, IEE, LGV, and RVR) were identified from HPH by extensive chemical hydrolysis (6 M HCl).…”
Section: Health Benefitsmentioning
confidence: 99%
“…Several reports in literature have confirmed the role of bioactive peptides as inhibitors of various metabolic enzymes and with potential use as therapeutic agents against specific diseases. For example food protein‐derived peptides act as antihypertensive agents by inhibiting angiotensin‐converting enzyme (Sanchez‐Rivera et al ., ; Ciau‐Solis et al ., ) and renin activities (He et al ., ; Girgih et al ., ). Peptides also possess antioxidative properties (Jara et al ., ; Ma et al ., ), whereas some sequences act as anti‐cancer agents by inhibiting excessive cell proliferation (Chi et al ., ; Vasquez‐Villanueva et al ., ).…”
Section: Introductionmentioning
confidence: 99%